Neo-Liberalism or Democracy? Economic Strategy, Markets, and Alternatives for the 21st Century - MacEwan, Arthur (Australia Pluto Press, 1999)
"Is it true that there is no alternative to the neo-liberal ideology of free trade, deregulation of markets, and government abandonment of social programs? Must we accept, in the name of globalization, the relentless pressure to reduce wages and cut social spending? Can poor countries pursue no other route to development but opening their economies to global forces?"--BOOK JACKET. "The author sets out to explore
Includes Index and References.
Keywords: Democracy -- Free Enterprise -- Liberalism